2020
DOI: 10.21203/rs.3.rs-16895/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for lymph node metastasis and surgical methods in patients with early-stage peripheral lung adenocarcinoma presenting as ground glass opacity

Abstract: Background It is difficult to predict lymph node metastasis in patients with early lung cancer. Pure ground glass opacity (GGO) on computed tomography indicates an early-stage adenocarcinoma that can be removed by limited resection or lobectomy without the need for mediastinal lymph node dissection or sampling, and lung adenocarcinoma with GGO therefore has a good prognosis. We examined the incidence and risk factors of lymph node metastasis in patients with clinical stage IA lung adenocarcinoma. Methods We re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
2
1
1
Order By: Relevance
“…In this study, 12 (1.8%) patients had single N2 metastasis, of which 3 patients had the smallest consolidation size of 10mm, and the tumors were all located in the upper lobe of the left lung (Patient One had 1 lymph node metastasis in 6 stations, and Patient Two had 1 lymph node metastasis in 6 stations and 1 lymph node in 9 stations, Patient Three had 1 lymph node metastasis in 5 stations and 1 lymph node metastasis in 6 stations). In consistent with the study by Wang et al [17] reporting 1.5% of single N2 metastasis, our ngdings suggest that N2 metastasis may appear in patients with early-stage NSCLC, and the absence of N1 metastasis cannot completely exclude N2 metastasis. Alternatively, it can be reckoned that patients with early NSCLC may have N2 metastasis without N1 metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, 12 (1.8%) patients had single N2 metastasis, of which 3 patients had the smallest consolidation size of 10mm, and the tumors were all located in the upper lobe of the left lung (Patient One had 1 lymph node metastasis in 6 stations, and Patient Two had 1 lymph node metastasis in 6 stations and 1 lymph node in 9 stations, Patient Three had 1 lymph node metastasis in 5 stations and 1 lymph node metastasis in 6 stations). In consistent with the study by Wang et al [17] reporting 1.5% of single N2 metastasis, our ngdings suggest that N2 metastasis may appear in patients with early-stage NSCLC, and the absence of N1 metastasis cannot completely exclude N2 metastasis. Alternatively, it can be reckoned that patients with early NSCLC may have N2 metastasis without N1 metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…Kim et al 19 reported that the 5-year disease-free recurrence risk of papillary predominant (OR= 2.49, P<0.001) and solid predominant (OR=1.99, P=0.003) is higher than that of other types of lung adenocarcinoma. Wang et al 15 (OR=1.574, P=0.001) and Ye et al 10 (OR=2.493, P=0.004) showed that pathological subtype was an important risk factor for mediastinal lymph node metastasis of stage IA lung adenocarcinoma, complying with the results of our study. For these two special types of lung adenocarcinoma above, systematic lymph node dissection should be the prior choice.…”
Section: Discussionsupporting
confidence: 91%
“…Lee et al 14 have shown that the abnormal CEA level is closely related to the distant metastasis of nonsmall cell lung cancer. Our results showed that the mediastinal lymph node metastasis rate in patients with CEA (>5ng/ml) was 57.89% (22/38), however, Wang et al 15 reported mediastinal lymph node metastasis rate in patients with CEA (>5ng/ml) was 15.25%, and it was a risk factor for lymph node metastasis (OR=1.574, P=0.001). Ye et al 10 also showed that the lymph node metastasis rate of CEA (>5ng/ml) was 19.16%, and it was a risk factor for lymph node metastasis in stage IA lung adenocarcinoma (OR=3.923, P<0.001), Koike et al 11 revealed that preoperative CEA(>3.5ng/ml) was a risk factor for mediastinal lymph node metastasis of clinical stage IA non-small cell lung cancer.…”
Section: Discussioncontrasting
confidence: 67%
“…To explain further, worse outcomes were expected for T2 stage patients compared to those with T1 as it is associated with a more serious tumor burden. The absence of a tumor thrombosis acted as a negative factor in recurrence and/or metastasis, and in patients with NSCLC, a tumor thrombosis is believed to be a predictor of poor prognosis as it is regarded as a prerequisite for tumor invasion of the vascular system or lymph node metastasis (27,28). Some studies have even suggested that tumor thromboses should be considered in TNM staging (29).…”
Section: Discussionmentioning
confidence: 99%